I. Ivkovic-Kihic, M. Read, Sh. Rane, A. Kovacevic. «Compressors and their systems». Post conference report / trans. from Engl. M. A. Fedorova - M. A. Fedorova (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение")
The article presents an overview report of the 12th International Conference on Compressors and their systems which was held in a hybrid format from September 6 to 8, 2022 in the City, University of London, UK. At this prestigious scientific and educational forum, within the framework of the plenary session, world experts made reports in the field of compressor technology and de-carbonization, as well as presentations at several technical and panel sessions on such topics as screw, scroll, vane and piston compressors; compressor systems and their diagnostic and control systems; turbo-machines; mathematical modeling and optimization of compressors, expanders and their systems. In addition, within the framework of the conference, a traditional short training course and a Forum on CFD (gas dynamic calculations) in rotary positive displacement machines were held. The introductory session was devoted to the basics of CFD implementation using the finite volume method. New studies in the field of CFD in rotary volumetric machines were presented, including those based on such programmes as ANSYS Forte and OpenFOAM. Complex modeling approaches, such as SCORG and GT-Suite, also attracted the attention of participants. Information about the next conference on Compressors and their systems, which will be held in 2023, is presented.